2018
DOI: 10.3389/fmicb.2018.00802
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Analyses of the Deteriorated Storeroom Objects in the Tianjin Museum Using Culture-Independent and Culture-Dependent Approaches

Abstract: In the storeroom C7 of the Tianjin Museum, one wooden desk and two leather luggages dated back to Qing dynasty (1644-1912 AD) presented viable microbial contamination. The aim of the present study was to investigate microbial communities responsible for the biodeterioration of storeroom objects using a combination of culture-independent and culture-dependent methods as well microscopic techniques. Scanning electron microscopy (SEM) revealed that the microflora on three storeroom objects were characterized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
0
31
1
Order By: Relevance
“…The dominant contaminant fungi belonged to the genus Penicillium, followed by Aspergillus and Cladosporium [32]. The genera Penicillium, Aspergillus and Chaetomium have been detected on organic objects such as wooden square stools and suitcases in a museum [6]. Piotrowska et al observed that the most important degrading component taxa were fungi of the genera Penicillium and Cladosporium [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant contaminant fungi belonged to the genus Penicillium, followed by Aspergillus and Cladosporium [32]. The genera Penicillium, Aspergillus and Chaetomium have been detected on organic objects such as wooden square stools and suitcases in a museum [6]. Piotrowska et al observed that the most important degrading component taxa were fungi of the genera Penicillium and Cladosporium [33].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the PCR products were used for library construction, and sequencing was performed on the Illumina HiSeq2500 PE250 platform. Specific methods of operation can be found in the literature described by Liu et al [6].…”
Section: High-throughput Sequencing Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This peculiar organism is an obligate xerophilic fungus with high tolerance to water stress. The minimum water activity for its germination and growth of this 0.675, and growth does not occur above 0.935 [26]. Recently, it has been associated with paper and books biodeterioration in museums, libraries or archives [13,27].…”
Section: State Of Conservation: Focus On Biological Analysesmentioning
confidence: 99%
“…Recently, the dark-stained deterioration has been discovered in some parts of the unique medieval murals of Saint Sophia's Cathedral in Kyiv, Ukraine, which could be caused by micromycetes. The knowledge of the nature of deterioration and the microorganisms involved is essential for fighting microbial invasion and saving cultural and historical heritage [1][2][3][4][5].…”
mentioning
confidence: 99%